Applicability of the Appropriate use Criteria for Myocardial Perfusion Scintigraphy - Oliveira,Anderson de (2014)
Background: Appropriateness Criteria for nuclear imaging exams were created by American College of Cardiology (ACC) e American Society of Nuclear Cardiology (ASNC) to allow the rational use of tests. Little is known whether these criteria have been followed in clinical practice. Objective: To evaluate whether the medical applications of myocardial perfusion scintigraphy (MPS) in a private nuclear medicine service of a tertiary cardiology hospital were suitable to the criteria of indications proposed by the American medical societies in 2005 and 2009 and compare the level of indication of both. Methods: We included records of 383 patients that underwent MPS, November 2008 up to February 2009. Demographic characteristics, patient's origin, coronary risk factors, time of medical graduation and appropriateness criteria of medical applications were studied. The criteria were evaluated by two independent physicians and, in doubtful cases, defined by a medical expert in MPS. Results: Mean age was 65 ± 12 years. Of the 367 records reviewed, 236 (64.3%) studies were performed in men and 75 (20.4%) were internee. To ACC 2005, 255 (69.5%) were considered appropriate indication and 13 (3.5%) inappropriate. With ACC 2009, 249 (67.8%) were considered appropriate indications and 13 (5.2%) inappropriate. Conclusions: We observed a high rate of adequacy of medical indications for MPS. Compared to the 2005 version, 2009 did not change the results.